2019
DOI: 10.1002/adom.201901247
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient, Simplified Monochrome and White Organic Light‐Emitting Devices based on Novel Exciplex Host

Abstract: along with a wide T 1 level, especially for blue phosphorescent OLEDs. [7,8] Recently, exciplex formed by an acceptor and a donor is seen as a promi sing candidate for using as a host in OLEDs because of its plastic transport capability and energy band gap. [9][10][11][12][13][14][15] Moreover, most exciplex systems exhibit thermally activated delayed fluorescence (TADF) process via reverse intersystem crossing (RISC), in which triplet excitons can be upconverted into singlet excitons arisen from their minor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…(3) The exciplex need to have a higher T1 level than phosphorescent dopants to restrain energy transfer from the phosphors to the exciplex. 28,29 According to the PL spectrum (S1=2.258 eV) and ΔE ST (0.022 eV) of the exciplex, T1 can be estimated to be about 2.236 eV, which is obviously lower than FSF4A (2.6 eV) and PO-T2T (3.0 eV). 40 Therefore, the red dye Ir(MDQ) 2 acac (2.0 eV) is used as a dopant to design red PhOLEDs based on the characteristics of a novel exciplex co-host.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) The exciplex need to have a higher T1 level than phosphorescent dopants to restrain energy transfer from the phosphors to the exciplex. 28,29 According to the PL spectrum (S1=2.258 eV) and ΔE ST (0.022 eV) of the exciplex, T1 can be estimated to be about 2.236 eV, which is obviously lower than FSF4A (2.6 eV) and PO-T2T (3.0 eV). 40 Therefore, the red dye Ir(MDQ) 2 acac (2.0 eV) is used as a dopant to design red PhOLEDs based on the characteristics of a novel exciplex co-host.…”
Section: Resultsmentioning
confidence: 99%
“…Sheng et al adopted exciplex cohost to achieve red phosphorescent OLEDs with maximum power efficiency of 35.3 lm W -1 and external quantum efficiency of 19.8%. 28 Xu et al reported a red phosphorescent OLED through exciplex cohost system with maximum power efficiency of 31.8 lm W -1 and turnon voltage of 2.24 V. 29 Yao et al realized a red phosphorescent device with a maximum power efficiency of 36.9 lm W -1 and external quantum efficiency of 15.5%. 30 However, despite the remarkable progress in the use exciplex co-hosts in OLEDs, it is still a great challenge to precisely predict the likelihood of electron hole pairs induce exciplex emission and achieve ultra-low turn-on voltage PhOLEDs.…”
Section: Introductionmentioning
confidence: 99%
“…When a phosphorescent UEML was inserted in heterojunction interface, a more efficient energy transfer occurs from interfacial exciplex to UEML dyes than the counterpart in non-exciplex-based devices ( Wu et al., 2019 ; Wang et al., 2019d ; Sheng et al., 2020 ). After understanding the luminescence mechanism of monochromatic OLEDs based on Donor/UEML/Acceptor structure, in 2020, Ma et al.…”
Section: Oleds With Uemls Inserted Into Nonluminous Materialsmentioning
confidence: 99%
“…Moreover, owing to small orbital overlap between the excited state and the ground state, most exciplex possess a small DEst (S 1 -T 1 energy splitting), which promotes the energy transfer process changing from Dexter energy transfer to Förster energy transfer in host-guest doping system. 8,[11][12][13][14][15][16][17] For example, Park et al 16 doped bis(2phenylpyridine)(acetylacetonato) iridium(III) (Ir(ppy) 2 acac) into the exciplex co-host formed by 4,4 0 ,4 00 -tri(N-carbazolyl) triphenylamine(TCTA) and bis-4,6-(3,5-di-3-pyridylphenyl)-2methylpyrimidine (B3PYMPM) to achieve green PhOLED with low turn-on voltage of 2.4 V and high external quantum efficiency (EQE) of 29.1% as well as low roll-off. Wang et al 17 employed interfacial exciplex of (N,N 0 -di(naphth-1-yl)-N,N 0diphenyl-benzidine (NPB)/1,3,5 tris[N-(phenyl) benzimidazole]-benzene (TPBi) as co-host to fabricate a red PhOLED showing a high EQE of 17.2% and a low turn-on voltage of 2.6 V simultaneously.…”
Section: Introductionmentioning
confidence: 99%